Linkage to hepatitis C treatment in two opioid substitution treatment units in Gothenburg, Sweden: a retrospective cohort study - Magdalena Ydreborg; Emil Lundström; Rosanna Kolleby; Sofia Lexén; Elena Pizarro; Jessica Lindgren; Rune Wejstål; Simon B. Larsson (BMC, 2023)
Abstract Background Chronic infection with the hepatitis C virus (HCV) is common in people with former or current injection drug use. Among the patients in the opioid substitution treatment (OST) program in Gothenburg, Sweden, more than 50% had been infected with HCV. However, many patients did not have any follow-up for their infection and the linkage to treatment could be improved. Methods A model of care for HCV was introduced at an OST unit in Gothenburg, Sweden, in 2017. The aim was to increase testing and linkage to HCV treatment. A nurse and a medical doctor, both specialized in infectious diseases, performed on-site testing at the OST unit with transient liver elastography (Fibroscan) to evaluate the fibrosis stage and initiated HCV treatment. This study retrospectively reviewed the patients' medical records to assess information regarding participation in the model of care, hepatitis C status, linkage to treatment and treatment outcome. Results Among the 225 patients enrolled in OST at baseline, 181 were still in the OST program at the end of study (December 31st, 2018). In total, 29 patients, most of whom did not attend the Clinic of Infectious Diseases, were referred to the model of care. By the end of study, 17 patients (100% of those treated) reached sustained virologic response. In parallel, an additional 19 patients got treatment directly at the Clinic of Infectious Diseases. Conclusion Integrating HCV screening and examination in an OST unit successfully linked patients to treatment. However, not all patients received treatment. To reach the goal of eliminating HCV, different models of care are needed.